2016
DOI: 10.3389/fpsyg.2016.01365
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Affective Information – An Evaluation of Repetition Suppression Effects

Abstract: Both theoretical proposals and empirical studies suggest that the brain interprets sensory input based on expectations to mitigate computational burden. However, as social beings, much of sensory input is affectively loaded – e.g., the smile of a partner, the critical voice of a boss, or the welcoming gesture of a friend. Given that affective information is highly complex and often ambiguous, building up expectations of upcoming affective sensory input may greatly contribute to its rapid and efficient processi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…shown to be less pronounced for emotional stimuli (e.g., Trapp & Kotz, 2016), which may have contributed to emotion effects in the active runs.…”
Section: Discussionmentioning
confidence: 93%
“…shown to be less pronounced for emotional stimuli (e.g., Trapp & Kotz, 2016), which may have contributed to emotion effects in the active runs.…”
Section: Discussionmentioning
confidence: 93%
“…For example, schizophrenia has been re-explained by deviant prediction error signaling (Horga et al 2014 ; Umbricht & Krljes 2005 ). Anxiety is an emotion that is inherently linked to the future, i.e., by expecting aversive things to happen, and has therefore consequently been associated with biased prediction processes (Grupe & Nitschke 2013 ; Trapp & Kotz 2016 ). Autism has been linked to aberrant predictive processes, in that these individuals perceive the world based on fewer expectations, thus are “flooded” with raw data from bottom-up, or handle prediction errors less flexibly (Pellicano & Burr 2012 ; van de Cruys et al, 2014 ).…”
Section: The Brain As a Prediction Devicementioning
confidence: 99%
“…First evidence for this idea was provided by Summerfield, Trittschuh, Monti, Mesulam, and Egner (2008) who found that the RS effect was modulated by the likelihood of a repetition, which would not occur if the effect is entirely driven by (low-level) neural fatigue or adaptation effects. There is evidence that RS also changes as a function of the stimulus’ valence (for a review see Trapp & Kotz, 2016). Expectation effects of RS are usually automatic and participants report no awareness of repetition likelihoods (Grotheer & Kovács, 2016).…”
Section: Empathy Top-down Processes and Expectationsmentioning
confidence: 99%